Rust - Stavely, J.R.; Pastor Corrales, Marcial A. (International Center for Tropical Agriculture, 1989)
Bean rust (Uromyces phaseoli), a common disease with worldwide distribution, is considered one of the most important bean production problems in the tropics. Prolonged periods of moisture and moderate temp. (17-27 degrees C) favor disease development. The infection process begins when a urediospore produces a germ tube, which develops an appressorium after physical contact with the edges of a stomata. The fungus may infect leaves and pods, and rarely stems and branches. For efficient disease control, cultural practices, crop rotation, elimination of harvest debris, biological control, the utilization of chemical products during the initial stages of plant development, and the use of resistant var. are recommended. A table is included on differential var. and infection rates used by different investigators to identify physiological races of this pathogen. Symptoms and damage caused by the disease are illustrated in color. (CIAT)